Suicide risk profiles and barriers to professional help-seeking among college students with elevated risk for suicide. (August 2022) - Bornheimer, Lindsay A.; Czyz, Ewa; Koo, Hyun Jung; Li Verdugo, Juliann; Eisenberg, Daniel; Zheng, Kai; Pistorello, Jacqueline; Albucher, Ronald C.; Coryell, William; Favorite, Todd; King, Cheryl A.
Abstract: Suicide is the second leading cause of death among college students, yet many students with elevated suicide risk do not seek professional help. This study identified suicide risk profiles among college students and examined these in relation to students' perceived barriers to professional help-seeking. Data were obtained from college students (n = 1689) identified to be at elevated risk for suicide based at four US universities. Latent class analysis was performed to determine risk profiles, followed by examinations of differences in help-seeking barriers by profile groupings. Results revealed three student groupings: (1) moderate internalizing and externalizing symptoms (with low alcohol misuse), (2) highest internalizing and externalizing symptoms (with highest social disconnection), and (3) lowest internalizing symptoms and low externalizing (with highest social connection and alcohol misuse). Group 1 included the youngest and most racially and sexually diverse students, Group 2 endorsed the most help-seeking barriers, and Group 3 endorsed the fewest barriers. Group 2 is especially concerning, considering the severe clinical characteristics, high number of barriers, and low connectedness to others for potential support. Understanding these differences across risk and barrier profiles is an important step towards developing tailored approaches to increase mental health care in college populations.